The impact of supply chain cost on the price of the final product - Lapinskaitė, Indrė; Kuckailytė, Justina (Business, Management and Economics Engineering, 2014)
Nowadays, as consumption and production are growing enormously fast, companies are seeking for costs reduction aimed at ensuring competitiveness. In manufacturing companies, supply chain expenses play a colossal role in the cost of the final product. This paper focuses on the main processes in the logistics chain and their components. The authors analyse the relationship between the supply chain expenses and the price of the final product, the classification of logistics chain costs and their minimization as an assumption for the competitiveness of the final price.